Dual NHC/photoredox catalytic synthesis of 1, 4-diketones using an MR-TADF photocatalyst (DiKTa). Issue 98 (21st November 2022) - Prentice, Callum; Morrison, James; Zysman-Colman, Eli; Smith, Andrew D.
Abstract : The use of the recently reported organic multi-resonant thermally activated delayed fluorescent (MR-TADF) photocatalyst DiKTa allows for the modular synthesis of 1, 4-diketones under mild and metal-free conditions. Abstract : The use of the recently reported organic multi-resonant thermally activated delayed fluorescence (MR-TADF) photocatalyst DiKTa allows for the modular synthesis of 1, 4-diketones under mild and metal-free conditions. The reaction proceeds via a three-component relay process in the presence of an N-heterocyclic carbene (NHC) organocatalyst.